Factors Affecting Seed Germination of Feather Fingergrass (Chloris virgata). Issue 4 (December 2016) - Fernando, Nimesha; Humphries, Talia; Florentine, Singarayer K.; Chauhan, Bhagirath S.
Abstract : Laboratory experiments were carried out to determine the effect of several environmental factors on seed germination of feather fingergrass, one of the most significant emerging weeds in warm regions of the world. Seed germination occurred over a broad range of temperatures (17/7, 25/10, and 30/20 C), but germination being highest at alternating temperatures of 30/20 C under both 12 h light/12 h dark and 24 h dark conditions. Although seed germination was favored by light, some seeds were capable of germinating in the dark. Increasing salt stress decreased seed germination until complete inhibition was reached at 250-mM sodium chloride. Germination decreased from 64 to 0.7% as osmotic potential decreased from 0 to −0.4 MPa, and was completely inhibited at −0.6 MPa. Higher seed germination (> 73%) was observed in the range of pH 6.4 to 8 than the other tested pH levels. Heat shock had a significant effect on seed germination. Germination of seeds placed at 130 C for 5 min was completely inhibited for both dry and presoaked seeds. The results of this study will help to develop protocols for managing feather fingergrass, and to thus avoid its establishment as a troublesome weed in economically important cropping regions.